Values at Work: Employee Participation Meets Market Pressures at Mondragon - Strauss, George (Relations industrielles / Industrial Relations, 2000)
Values at Work: Employee Participation Meets Market Pressures at Mondragon, by George Cheney, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Cooperatives; Labor Unions; Labor relations; Market strategy; Participatory management; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z